GIANT CELL TUMOR OF THE RIGHT DISTAL FEMUR REGION IN A MALE 25 YEARS OLD WITH HIV POSITIVE (RARE CASE) - Muhammad Riyadli; Mujaddid Idulhaq; Pamudji Utomo (Universitas Muhamadiyah Surakarta, 2019)
Giant cell tumor (GCT) with Human Immunodeficiency Virus (HIV) infection is a rare case. At present, few literatures reported about GCT with HIV positive patients and there are no effective treatments of this disease currently. The aim of this article is to report the change the surgical treatment from limb salvage (wide excision and endoprostheses) to another way limb salvage (wide excision and knee arthrodesis) to minimize risk and further complication. A case of male, 25 years old, with diagnosis GCT of the right distal femur with HIV positive. In this case we administered antiretroviral treatment (ARV) and planned to limb salvage surgery (wide excision and knee arthrodesis).We follow up this patient in the first 4 weeks. There were no complaints, good postoperative wounds, no signs of infection, and histopathological examination postoperative showed the positive results of a GCT. The conclusion the surgical treatment from limb salvage (wide excision and endoprostheses) to another way limb salvage (wide excision and knee arthrodesis) could minimize risk and further complication.Keywords: Giant Cell Tumor, HIV,Limb Salvage Surgery, Wide Excision, Arthrodesis KneeGiant Cell Tumor (GCT) disertai dengan infeksi Human Imminodeficiency Virus (HIV) merupakan kasus yang jarang terjadi. Pada saat ini hanya sedikit literatur yang melaporkan kejadian pasien GCT dengan HIV positif dan belum ada standar terapi yang efektif. Tujuan dari artikel ini adalah melaporkan penggantian penatalaksanaan operatif sebelumnya berupa limb salvage (eksisi luas dan pemasangan endoprosthesis) menjadi eksisi luas dan arthrodesis knee untuk meminimalisir risiko dan kompikasi lebih lanjut. Kasus seorang laki-laki usia 25 tahun dengan diagnosis GCT pada distal femur kanan dengan infeksi HIV positif. Pada kasus ini, terapi yang diberikan adalah Anti Retroviral (ARV) dan operatif dengan limb salvage (eksisi luas dan arthrodesis lutut). Follow up pasien ini pada 4 minggu pertama post operasi. Keluhan nyeri berkurang, luka operasi baik, tidak ada tanda infeksi dan pemeriksaan histopatologi menunjukkan hasil GCT.Kesimpulannya bahwa penatalaksanaan operatif sebelumnya berupa limb salvage (eksisi luas dan pemasangan endoprosthesis) menjadi eksisi luas dan arthrodesis knee dapat meminimalisir risiko dan kompikasi lebih lanjut. Kata Kunci: Giant Cell Tumor, Hiv, Limb Salvage, Eksisiluas, Arthrodesis Lutut